PENDAMPINGAN PEMBELAJARAN HAFALAN AL QURAN MENGGUNAKAN INOVASI GERAKAN TANGAN DI DESA BULUSULUR - Ruslina Dwi Wahyuni; Sulastri (LPPM STAIMAS WONOGIRI, 2022)
This devotion aims to increase the attractiveness of students to learn to memorize Juz'Amma so that it has an impact on increasing the reading of the Qur'an. The target of this service is the students of the Qur'an Education Park in Malangsari Hamlet, Bulusulur Village. The innovation used in this service is the innovation of the Juz 'Amma memorization method with hand gestures. Techniques are performed with teaching, hands-on practice and documentation. The application of the purpose of the Juz'Amma memorization method with hand movements is to find out how much ease it is to memorize Juz 'Amma with hand movements in students. The results of this devotion show that the application of Juz 'Amma memorization with hand movements greatly facilitates every teacher and child guide in memorization, makes it easier for children to remember the memorization that has been taught, understands the meaning of the memorized verses, trains children's motor physique through hand movements and brings children closer to their love for the Qur’an.